PERAN GURU DALAM UPAYA MENINGKATKAN KUALITAS BACA TULIS AL-QUR’AN DI TPQ MIFTAHUL ULUM NGLELE SUMOBITO JOMBANG - Ali Muhsin (Universitas Yudharta Pasuruan, 2019)
The effort to improve Al-Qur'an reading and writing becomes the main factor is the improvement of the quality of human resources that is teacher. Teachers have characteristics as mentors who are able to show the dynamic interaction between teachers and learners. The purpose of the study to know how the role of teachers in an effort to improve the quality of literature Al-Qur`an in TPQ Miftahul Ulum Nglele Sumobito Jombang. This type of descriptive qualitative research with interview method, observation and documentation. Analytical techniques using data reduction (data reduction), data display (data presentation), data conclusing drawing / verification. In reading the Qur'an the learner is not a thing that goes without a process, but requires a concrete teacher's efforts. The result of the teacher's role in the effort to improve the literacy of the Qur'an is very satisfactory as evidenced by the santri can read Al-Qur an well and correctly.